2019
DOI: 10.3390/biom9100558
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Biological Activities of Artemisia pedemontana subsp. assoana Essential Oils and Hydrolate

Abstract: Given the importance of the genus Artemisia as a source of valuable natural products, the rare plant Artemisia pedemontana subspecies assoana, endemic to the Iberian Peninsula, has been experimentally cultivated in the greenhouse and aeroponically, to produce biomass for essential oil (EO) extraction. The chemical composition of the EOs was analyzed, and their plant protection (insects: Spodoptera littoralis, Rhopalosiphum padi, and Myzus persicae; plants: Lactuca sativa and Lolium perenne; fungi: Aspergillus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…However, only few studies have been carried out on EOs and Hys obtained from the same distillation process in order to compare their chemical composition [ 9 , 10 , 11 ], or study some of their activities such as psychopharmacological and anti-cancer activities [ 12 , 13 ], or larvicidal and nematodicidal ones [ 14 , 15 ]. Our group participated in these early investigations, assessing the chemical composition and the antimicrobial activity of the EO and Hy obtained from Monarda citriodora in a recent research.…”
Section: Introductionmentioning
confidence: 99%
“…However, only few studies have been carried out on EOs and Hys obtained from the same distillation process in order to compare their chemical composition [ 9 , 10 , 11 ], or study some of their activities such as psychopharmacological and anti-cancer activities [ 12 , 13 ], or larvicidal and nematodicidal ones [ 14 , 15 ]. Our group participated in these early investigations, assessing the chemical composition and the antimicrobial activity of the EO and Hy obtained from Monarda citriodora in a recent research.…”
Section: Introductionmentioning
confidence: 99%
“…Anyway, the EOs from O. virens, S. lavandulifolia, O. vulgare, O. majorana, S. officinalis and S. sclarea indicated above have shown much greater efficacy, since they maintain their activity at much lower concentrations (even 125 μg/ml). In the study by Sainz et al [24] the main components from A. pedemontana tested (1.8 cineole and camphor) showed no activity, alone or in combination. The main components (% abundance � 1) of the EOs analyzed in the present study are shown in Table 3.…”
Section: Resultsmentioning
confidence: 93%
“…There are hardly any studies on the activity of natural products on P. davidi. In a recent study, [24] Sainz et al tested the activity of two essential oils from Artemisia pedemontana subsp. assoana experimentally cultivated in the greenhouse and aeroponically, as well as their main components, on this parasite.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Essential oils (EOs) and aromatic oily compounds extracted from plant material, have been suggested as potential sources of new antimicrobial and therapeutic products [1][2][3][4][5]. In nature, EOs play a role in plant defence against microorganisms and insects [6]. In addition, they are valuable natural compounds used in many fields, i.e.…”
Section: Introductionmentioning
confidence: 99%